1979
DOI: 10.1177/002194367901600204
|View full text |Cite
|
Sign up to set email alerts
|

Communication Difficulties as Perceived By the Accounting Profession and Professors of Accounting

Abstract: In an effort to bridge the gap between classroom experience and "real world" activity, the authors developed a survey instrument for measuring the accounting professional's expectations of the newly hired employee's communication skills. After collecting the results of the survey, including responses from accounting educators and recently graduated accountants, the authors were able to conclude that some general agreement did exist about the communication needs of accountants: most lack the skill to articulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…A study was conducted in the USA by Andrews and Koester (1979) to determine the differences in the perceptions of academics, employers and graduate accountants with regard to the communication skills necessary in accounting. They concluded that while academics and employers had similar perceptions, employers and new graduate accountants had significantly different perceptions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study was conducted in the USA by Andrews and Koester (1979) to determine the differences in the perceptions of academics, employers and graduate accountants with regard to the communication skills necessary in accounting. They concluded that while academics and employers had similar perceptions, employers and new graduate accountants had significantly different perceptions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…But to succeed in the pedagogical communication of financial information there is also a need for non-numeric reporting. Andrews and Koester (1979), for example, emphasise "the significance of these nonnumerical reports". To work with a more active reporting, it is important that the financial reporting is supplemented with a non-financial/non-numeric reporting.…”
Section: Financial Reports -The Written Documentsmentioning
confidence: 99%
“…But this does not exclude that the form of communication is important. A core competence of an accountant is the ability to formulate a concept and thus a meaning (Andrews & Koester, 1979). The concepts are means to convey and communicate a deeper meaning, where for example a budget is not just a compilation of numbers but also an expression of responsibility and authority (Emmanuel, Otley, & Merchant, 1990).…”
Section: The Content Of the Communication -Concepts And Illustrationsmentioning
confidence: 99%
See 2 more Smart Citations